Assessment of yield performances for grain sorghum varieties by AMMI and GGE biplot analyses - Wang, Runfeng; Wang, Hailian; Huang, Shaoming; Zhao, Yingxing; Chen, Erying; Li, Feifei; Qin, Ling; Yang, Yanbing; Guan, Yan’an; Liu, Bin; Zhang, Huawen (Frontiers in Plant Science, 2023)
Grain sorghum is an exceptional source of dietary nutrition with outstanding economic values. Breeding of grain sorghum can be slowed down by the occurrence of genotype × environment interactions (GEI) causing biased estimation of yield performance in multi-environments and therefore complicates direct phenotypic selection of superior genotypes. Additive main effects and multiplicative interaction (AMMI) and genotype + genotype × environment (GGE) biplot models allow uncovering GEI patterns and effective identification of high-yielding genotypes with stable performance across environments. Multi-environment trials were carried out on 13 newly developed grain sorghum varieties at seven test locations across China for two years. Randomized complete block design was used in field trials with three replications. Yield (YLD), plant height (PH), days to maturity (DTM), thousand seed weight (TSW), and panicle length (PL) were measured. Joint analysis of variance revealed significant effects of genotype, environment, and GEI on YLD, PH, DTM, TSW, and PL (p < 0.001). Broad-Formatted: Font: Italic sense heritability estimates for these traits varied from 0.40 to 0.94 within the medium to high range. To analyze yield performances and stability among tested varieties, AMMI stability estimates, AMMI biplots and GGE biplots were utilized. AMMI model identified two significant interaction principal component axes (IPCAs) accounting for 66.3% of total variance, whereas the first two principal components (PC1 and PC2) in GGE biplot explained 71.39% of total variation caused by GEI. According to AMMI stability estimates, AMMI biplots, GGE biplots, G3 (Liaoza No.52) and G10 (Jinza 110) were identified as the superior varieties, and G3 was regarded as the most stable highyielding variety extensively adapted to all environments. Furthermore, GGE biplot analysis classified test locations into two groups and identified best varieties for each group of locations, i.e., G11 (Jinza 111) was the ideal variety suitable for Yili while G3 showed wide adaptability in the other locations. Based on average yield performances of the varieties across the environments, G3 was the most stable variety with highest yielding potential while G10 was second to G3 in average yield and stability. We recommend G3 for the production in Shenyang,